Effect of CTGF/CCN2 on Osteo/Cementoblastic and Fibroblastic Differentiation of a Human Periodontal Ligament Stem/Progenitor Cell Line. Issue 1 (January 2015) - Yuda, Asuka; Maeda, Hidefumi; Fujii, Shinsuke; Monnouchi, Satoshi; Yamamoto, Naohide; Wada, Naohisa; Koori, Katsuaki; Tomokiyo, Atsushi; Hamano, Sayuri; Hasegawa, Daigaku; Akamine, Akifumi
<x xml:space="preserve">Abstract</x> Appropriate mechanical loading during occlusion and mastication play an important role in maintaining the homeostasis of periodontal ligament (PDL) tissue. Connective tissue growth factor (CTGF/CCN2), a matricellular protein, is known to upregulate extracellular matrix production, including collagen in PDL tissue. However, the underlying mechanisms of CTGF/CCN2 in regulation of PDL tissue integrity remain unclear. In this study, we investigated the effect of CTGF/CCN2 on osteo/cementoblastic and fibroblastic differentiation of human PDL stem cells using the cell line 1–11. CTGF/CCN2 expression in rat PDL tissue and human PDL cells (HPDLCs) was confirmed immunohisto/cytochemically. Mechanical loading was found to increase gene expression and secretion of CTGF/CCN2 in HPDLCs. CTGF/CCN2 upregulated the proliferation and migration of 1–11 cells. Furthermore, increased bone/cementum‐related gene expression in this cell line led to mineralization. In addition, combined treatment of 1–11 cells with CTGF/CCN2 and transforming growth factor‐β1 (TGF‐β1) significantly promoted type I collagen and fibronectin expression compared with that of TGF‐β1 treatment alone. Thus, these data suggest the underlying biphasic effects of CTGF/CCN2 in 1–11 cells, inducible osteo/cementoblastic, and fibroblastic differentiation dependent on the environmental condition. CTGF/CCN2 may contribute to preservation of the structural integrity of PDL tissue, implying its potential use as a therapeutic agent for PDL regeneration. J. Cell. Physiol. 229: 150–159, 2014. © 2014 Wiley Periodicals, Inc.